2013
DOI: 10.1186/1477-7827-11-58
|View full text |Cite
|
Sign up to set email alerts
|

Is androgen production in association with immune system activation potential evidence for existence of a functional adrenal/ovarian autoimmune system in women?

Abstract: BackgroundLow functional ovarian reserve (FOR) is at all ages associated with low testosterone (T) levels. Causes are, however, unknown. We, therefore, investigate whether androgens with low FOR are associated with non-specific immune system activation.Methods322 infertile women with low and normal FOR (controls) were assessed with a broadly based immune profile, which in previous studies has proven effective in differentiating infertile patients with and without immune system activation. Patients were either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…CCL2 and other proinflammatory cytokines are negatively associated with testosterone serum levels in obese men . Recently, several studies have indicated that testosterone is a potent immunosuppressor that may negatively influence the recruitment of macrophages to tumor tissue at higher serum concentrations . This is the first study to show a gender‐specific effect of CCL2 and CX3CL1 mRNA expression on the disease‐specific survival of STS patients.…”
Section: Discussionmentioning
confidence: 67%
“…CCL2 and other proinflammatory cytokines are negatively associated with testosterone serum levels in obese men . Recently, several studies have indicated that testosterone is a potent immunosuppressor that may negatively influence the recruitment of macrophages to tumor tissue at higher serum concentrations . This is the first study to show a gender‐specific effect of CCL2 and CX3CL1 mRNA expression on the disease‐specific survival of STS patients.…”
Section: Discussionmentioning
confidence: 67%
“…Fully expecting a high degree of false-positivity, any positive finding in the panel is clinically considered to represent immune system activation, and only complete absence of any positive findings is clinically considered a quiescent immune system [11]. …”
Section: Methodsmentioning
confidence: 99%
“…Yet, somewhat counter intuitively, we also discovered that they demonstrated no evidence whatsoever of immune system activation as we initially had hypothesized; yet, young, healthy control patients with normal androgen levels, to some degree did demonstrate evidence of immune system activation [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested an autoimmune association with DOR [48,49,4,50]. Unfortunately, no standard exists for defining those with autoimmune features.…”
Section: Bone Morphogenetic Protein 15 (Bmp15)mentioning
confidence: 99%
“…Unfortunately, no standard exists for defining those with autoimmune features. Most studies have used only one positive autoimmune antibody to classify a patient as having abnormal autoimmune function [48,4,49].…”
Section: Bone Morphogenetic Protein 15 (Bmp15)mentioning
confidence: 99%